Penerapan Metode Project Based Learning pada Mata Kuliah Teknologi Pengelasan Logam di Jurusan Teknik Mesin FT-UNP - Fajri, Husnul; Purwantono, Purwantono; Irzal, Irzal; Wulansari, Rizky Ema (TSAQOFAH, 2023)
Learning as a learning process built by lecturers to develop creative thinking that can improve students' thinking skills. Project-based learning is a teaching and learning strategy that involves students to work on a project that is useful for solving community or environmental problems. The type of research used is research in the form of classroom action research. However, according to researchers, classroom teaching is not only in a room, but a group of students who are learning. This classroom action research can be done not only in the classroom, but anywhere, as long as there is a group of students who are learning. This study aims to see the results of the application of Project-based learning in Welding Technology Subjects with 29 students of the Department of Mechanical Engineering FT-UNP. The aspects seen in the observation results are visual, oral, listening, writing, monotoric, mental, emotional activities. Aspects seen in student learning outcomes include: project worksheets and assessment sheets. The results of the recapitulation of observation of activeness in Cycle I averaged 60.16% and the percentage of activeness in Cycle II averaged 80.56%. The overall average liveliness between cycles is 70.4% and learning outcomes are 79.65%. Based on the results of classroom action research that has been carried out in 2 (two) cycles in this study, it can be concluded that the application of the project-based learning model can improve learning activeness and learning outcomes of Welding Technology courses of Mechanical Engineering Department Students FT-UNP.